Enhancing Halal Certification via Self-Declaration for MSMEs in Indonesia: The Pioneering Role of BMT NU Ngasem in Streamlining Processes - Laila Nur Sholikhah; Nasrulloh; Shang-Jin Wei (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2024)
This research aims to determine the role of BMT NU Ngasem in accelerating halal certification through self-declaration for MSMEs in Bojonegoro, and also the response of BMT NU to the halal certification self-declaration scheme for MSMEs in Bojonegoro. This type of research uses qualitative research methods with a descriptive approach. Research data is in the form of primary and secondary data. Primary data was obtained from interviews. Meanwhile, secondary data was obtained from websites and journals. Acceleration of halal certification given to Micro and Small Enterprises by BMT NU Ngasem, namely with the self-declare scheme. Where self declare is an independent statement of the halal status of MSE products. Business actors can self-declare if they have fulfilled the requirements, where the condition is that there must be assistance from a registered halal product process assistant. The potential success of the free halal certification acceleration program or what is usually called self-declaration by BMT NU Ngasem is supported by the large potential of the halal industry in Bojonegoro Regency. In this case BMT NU Ngasem has a role, namely as a companion to the halal product process. BMT NU Ngasem has a role, namely as a companion to the halal product process . which was founded in early 2023. Acceleration of halal certification given to Micro and Small Enterprises by BMT NU Ngasem, namely halal certification with a self-declare scheme. The response from BMT NU Ngasem to halal certification was very responsive to the halal certification program. It is proven by the data mentioned that 20 MSMEs have received a unified licensing process.